Factors Related to the Level of Compliance with Pulmonary TB Treatment - Martini, Endang; Sarfika, Rika; Yuliharnim, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Disobedience to the treatment of tuberculosis (TB) is the most important cause of the bad results of TB treatment, and improving support for TB patients are priority of main government, however, only There is little study about the impact of policy on family, social, and national. factor supporter obedience TB treatment. Study This evaluates obedience treatment in between TB patients (1). Studies published between 201 6 and 2023 were systematically reviewed through identification in the Research Gate, Science Direct, PubMed, and Google Scholar databases. Studies that met the inclusion criteria were included for review. The results of the literature review of the articles carried out can be concluded that the factor related factors​ with level obedience pulmonary TB treatment.